Crossed source-detector geometry for a novel spray diagnostic: Monte Carlo simulation and analytical results - Berrocal, Edouard; Churmakov, D. Y.; Romanov, V. P.; Jermy, Mark C.; Meglinski, I. V. (Osa Optical Society of America, 2005)
Sprays and other industrially relevant turbid media can be quantitatively characterized by light scattering. However, current optical diagnostic techniques generate errors in the intermediate scattering regime where the average number of light scattering is too great for the single scattering to be assumed, but too few for the diffusion approximation to be applied. Within this transitional single-to-multiple scattering regime, we consider a novel crossed source-detector geometry that allows the intensity of single scattering to be measured separately from the higher scattering orders. We verify Monte Carlo calculations that include the imperfections of the experiment against analytical results. We show quantitatively the influence of the detector numerical aperture and the angle between the source and the detector on the relative intensity of the scattering orders in the intermediate single-to-multiple scattering regime. Monte Carlo and analytical calculations of double light-scattering intensity are made with small particles that exhibit isotropic scattering. The agreement between Monte Carlo and analytical techniques validates use of the Monte Carlo approach in the intermediate scattering regime. Monte Carlo calculations are then performed for typical parameters of sprays and aerosols with anisotropic (Mie) scattering in the intermediate single-to-multiple scattering regime.
Keywords: Atmospheric and ocean optics : Aerosols; Geometrical optics : Geometrical optics, inhomogeneous media; Instrumentation, measurement, and metrology : Combustion diagnostics; Scattering : Multiple scattering; Scattering : Turbid media